Differential apoptotic gene expression in the male partners of infertile couples with normal and abnormal sperm parameters - Afsari, Maliheh; Talebi, Ali Reza; Tafti, Fatemeh Dehghani; Makki, Masoud; Fesahat, Farzaneh (JBRA assisted reproduction, 2022)
The purpose of this study was to investigate the cellular and molecular levels of apoptosis induction in three groups of male partners of infertile couples, one featuring subjects with normal sperm parameters and unexplained male infertility (UMI), one including men with abnormal sperm parameters, and one with fertile men as controls. Twenty-five infertile men with abnormal sperm parameters and 25 men with UMI and normal sperm parameters were recruited as experimental group I and experimental group II; 25 fertile men were included as controls. The mRNA levels of Fas, Fas ligand, Caspase 8, Bax, and Bcl2 were measured in the three groups. The cellular rates of early and late apoptosis were assessed using annexin V and propidium iodide staining. The expression of Bax, Bcl2, and the Bax/Bcl2 ratio in experimental group I was significantly higher than that in experimental group II and controls. However, the Bax/Bcl2 ratio was less than 1 among all groups. No significant difference was found among study groups regarding the gene expression of Fas, Fas ligand, and Caspase 8. No significant difference was seen in early apoptotic rates of sperm among study groups. The highest number of necrotic sperm cells was detected in experimental group I. The findings showed that the external pathways of apoptosis were not activated in the absence of external stimuli of sperm apoptosis in ejaculated sperm. Regardless of fertility status, apoptosis gene induction in the internal pathway was associated with abnormalities in sperm motility and/or morphology in men with abnormal parameters.